Intracellular accumulation of advanced glycation end products induces apoptosis via endoplasmic reticulum stress in chondrocytes. (1st March 2013) - Yamabe, Soichiro; Hirose, Jun; Uehara, Yusuke; Okada, Tatsuya; Okamoto, Nobukazu; Oka, Kiyoshi; Taniwaki, Takuya; Mizuta, Hiroshi
<x xml:space="preserve">Abstract</x> Mammalian cells attempt to maintain their homeostasis under endoplasmic reticulum (ER) stress. If the stress cannot be alleviated, cells are led to apoptosis through induction of C/EBP homologous protein (CHOP). ER stress is provoked in osteoarthritis chondrocytes, and intracellular accumulation of advanced glycation end products (AGEs) in chondrocytes is a possible cause. To clarify the role of intracellular AGE accumulation in chondrocytes, the present study investigated the effect of intracellular AGE accumulation on ER stress and apoptosis by in vitro and in vivo analysis. Intracellular AGE accumulation induced by AGE precursors caused apoptosis, induced expression of ER stress markers, and led to co‐localization of AGEs with glucose‐regulated protein 78, leading to formation of high‐molecular‐weight complexes in cultured chondrocytes. These reactions were inhibited by an AGE formation inhibitor. CHOP deletion inhibited apoptosis induced by intracellular AGE accumulation. In vivo intracellular AGE accumulation induced by intra‐articular injection of AGE precursors caused ER stress and apoptosis in chondrocytes and led to degradation of articular cartilage. Additionally, intracellular AGE accumulation increased the degree of cartilage degradation in an osteoarthritis model. These data indicate that intracellular accumulation of AGEs induces modification of unfolded protein response‐related protein by AGEs and apoptosis via ER stress in chondrocytes. Moreover, the in vivo study showed that intracellular AGE accumulation in chondrocytes is involved in the occurrence and progression of osteoarthritis through ER stress. Thus, research on mechanisms of apoptosis via ER stress induced by intracellular AGE accumulation in chondrocytes will lead to a new understanding of osteoarthritis pathology.